1985
DOI: 10.1073/pnas.82.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Immunophotoelectron microscopy: the electron optical analog of immunofluorescence microscopy.

Abstract: The electron optical analog of immunofluorescence microscopy combines three developments: (i) photo-electron microscopy to produce a high-resolution image of exposed components of the cell, (ii) site-specific antibodies, and (iii) photoemissive markers coupled to the antibodies to make the distribution of sites visible. This approach, in theory, provides a way to extend the useful immunofluorescence microscopy technique to problems requiring much higher resolution. The resolution limit of fluorescence microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Previous studies demonstrated that when fluorophores (fluorescein or rhodamine) and cAu 30 are attached to the same molecule (such as IgG or ligand), the fluorescence signal was quenched (Goodman, et al , 1991;Birrell, et al , 1985).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies demonstrated that when fluorophores (fluorescein or rhodamine) and cAu 30 are attached to the same molecule (such as IgG or ligand), the fluorescence signal was quenched (Goodman, et al , 1991;Birrell, et al , 1985).…”
Section: Discussionmentioning
confidence: 98%
“…Most fluorophores are small, compatible with biological samples and easily conjugated to different proteins or ligands. However, resolution attainable with LM is limited (Birrell et al , 1985). Therefore, subsequent EM imaging may be beneficial to obtain higher spatial resolution for structural studies (Nisman et al , 2004;Albrecht et al , 1993).…”
mentioning
confidence: 96%
“…The Oregon photoelectron microscope has been described (Griffith and Rempfer, 1987) and has been used to image a variety of biological specimens (Griffith and Birrell, 1985;Hedberg and Griffith, 1986;Habliston et al, 1986). In short, the microscope is an oil-free ultrahigh vacuum instrument utilizing liquid nitrogen temperature sorbtion prepumps and an ion pump for attaining final vacuum.…”
Section: Photoelectron Microscopymentioning
confidence: 99%
“…From a historical perspective, O. Hayes Griffith (4) was one of the pioneers of PEEM technology and applied the technique to biological samples in 1972 (4), reporting first PEEM images of rat epididymis. Griffith and his group realized the capabilities of PEEM as the electron-optics analog of fluorescence microscopy and used colloidal gold and silver enhanced colloidal gold particles to selectively label portions of a biologic with a higher spatial resolution (5)(6)(7). PEEM images for cells (8)(9)(10), viruses (11,12) and DNA (11,(13)(14)(15), among others (16)(17)(18), were reported using both labeling and nonlabeling techniques.…”
Section: Introductionmentioning
confidence: 99%